2003
DOI: 10.1086/344641
|View full text |Cite
|
Sign up to set email alerts
|

Models of Galaxy Clusters with Thermal Conduction

Abstract: We present a simple model of hot gas in galaxy clusters, assuming hydrostatic equilibrium and energy balance between radiative cooling and thermal conduction. For five clusters, A1795, A1835, A2199, A2390, and RX J1347.5À1145, the model gives a good description of the observed radial profiles of electron density and temperature, provided that we take the thermal conductivity to be about 30% of the Spitzer conductivity. Since the required is consistent with the recent theoretical estimate of Narayan & Medvedev … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
309
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(312 citation statements)
references
References 61 publications
1
309
2
Order By: Relevance
“…First, thermal conduction has the potential to be extremely important for the thermodynamic state of a CC (e.g., Voigt & Fabian 2004;Voit 2011). While it cannot by itself offset the radiative cooling in a stable manner (Stewart et al 1984;Bregman & David 1988;Soker 2003;Zakamska & Narayan 2003;Voigt & Fabian 2004;Pope et al 2006), it may provide part of the heating, reducing the burden on the AGN, and can aid in the isotropization of the AGN heating throughout the core. Second, the ICM is known to be magnetized with β∼100 (Carilli & Taylor 2002), where β is defined as the ratio between gas thermal pressure and magnetic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…First, thermal conduction has the potential to be extremely important for the thermodynamic state of a CC (e.g., Voigt & Fabian 2004;Voit 2011). While it cannot by itself offset the radiative cooling in a stable manner (Stewart et al 1984;Bregman & David 1988;Soker 2003;Zakamska & Narayan 2003;Voigt & Fabian 2004;Pope et al 2006), it may provide part of the heating, reducing the burden on the AGN, and can aid in the isotropization of the AGN heating throughout the core. Second, the ICM is known to be magnetized with β∼100 (Carilli & Taylor 2002), where β is defined as the ratio between gas thermal pressure and magnetic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works by Narayan & Medvedev (2001) and Gruzinov (2002) show that in the presence of turbulent magnetic fields, the conductivity can be as large as a fraction of the Spitzer value and thus can play a significant role in balancing cooling flows. As a consequence, thermal conduction has recently been reintroduced as a possible heat source to balance the energy losses (see, e.g., Voigt et al 2002;Voigt & Fabian 2004;Fabian et al 2002;Malyshkin 2001;Zakamska & Narayan 2003). However, as we discuss in more detail in x 5.1, thermal conduction fails in supplying the needed heat in the central regions (see also Voigt et al 2002;Voigt & Fabian 2004;Zakamska & Narayan 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, all the models predicting that radiative cooling is balanced only by energy input from the central AGN fail (McNamara 2002;Zakamska & Narayan 2003;Brighenti & Mathews 2002). In particular, Brighenti & Mathews (2002) analyzed several heating mechanisms induced by the central AGN and concluded that no simple mechanism is able to quench the cooling flow.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a cool phase in cooling flows has proven a persistent puzzle. Recently, two main candidates for the heating of the gas in the central regions of clusters have emerged: (1) heating by outflows from active galactic nuclei (AGNs; Tabor & Binney 1993;Churazov et al 2001;Binney 2001;Bruggen & Kaiser 2002;Brü ggen 2003), and (2) transport of heat from the outer regions of the cluster by thermal conduction (Zakamska & Narayan 2003;Ruszkowski & Begelman 2002;Fabian et al 2001;Voigt et al 2002;Gruzinov 2002;Friaça 1986;Bertschinger & Meiksin 1986;Meiksin 1988;Bregman & David 1988).…”
Section: Introductionmentioning
confidence: 99%